Pengaruh Content Marketing, Online Customer Review, dan Online Customer Rating Terhadap Keputusan Pembelian Produk Paddy di Tiktok Shop - Ramadillah, Tsara Khalistha; Mubarok, Dadan Abdul Aziz (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The development of information technology and the increasing number of internet users, especially in Indonesia, have made social media a familiar source of information in society. As one of the most popular social media platforms in Indonesia, namely TikTok, TikTok presents the TikTok Shop feature that allows users not only to create content but also to make users sell directly. One of the local brands that utilizes this feature is Paddy. However, in 2024 data showed that Paddy's sales experienced a decline which was thought to be influenced by several factors, including Content Marketing, Online Customer Reviews, and Online Customer Ratings. This study aims to determine the effect of Content Marketing, Online Customer Reviews, and Online Customer Ratings on Paddy Product Purchase Decisions at TikTok Shop. The research method used is quantitative through a Google form questionnaire distributed to 100 respondents. The results of the study show that Content Marketing has a partial effect on Purchase Decisions, Online Customer Reviews have no partial effect on Purchase Decisions and Online Customer Ratings have no partial effect on Purchase Decisions. However, simultaneously Content Marketing, Online Customer Reviews, and Online Customer Ratings have a significant effect on Purchase Decisions.